Bone Transport over the Plate for the Segmental Bone Defect of Tibia - Il Seo; Chang-Wug Oh; Joon-Woo Kim; Kyeong-Hyun Park (Journal of Trauma and Injury)
Segmental bone defects of the tibia present a challenging problem for the orthopedic trauma surgeon. These injuries are often complicated by soft tissue defects and infection. Many techniques are reported, from bone graft to bone transport. To our knowledge, bone transport over the plate in the distraction site has not been described for the treatment of tibial bone defect. We report an instance including procedure and subsequent complications after bone transport over the plate, to restore a tibial bone defect.